The crucible screenplay - Miller, Arthur 1915-2005; Miller, Arthur 1915-2005. (New York, New York Penguin Books, 1996)
The masterpiece of American drama is now a major motion picture from 20th Century Fox, starring Daniel Day-Lewis, Winona Ryder, and Paul Scofield. Set during the witch hunts in Salem, Massachusetts, in 1692, The Crucible recounts the vengeance, mass hysteria, and collective evil that poisoned this small town. photos, some in color.
First published by the Viking Press in 1953.
Keywords: Trials (Witchcraft) -- Drama; Salem (Mass.) -- History -- Colonial period, ca. 1600-1775 -- Drama